A Twenty-Minute Nap Boosts the Planning Domain of Executive Function in Sleep Deprived Late Adolescents - Kang, Kyungmo; Choi, Juheon; Hwang, Hee-jin; Koo, Dae Lim; Kim, Jong Seung; Oh, Bumjo (Journal of sleep medicine, 2017)
Objectives: The positive effects of nap on cognitive function and memory have been researched intensively among children and adults. However, the relationship between afternoon nap and executive function among sleep deprived late adolescents has not been studied as much. Methods: Ten sleep deprived, otherwise healthy Korean high school students were recruited, and asked to fill out Pittsburgh Sleep Quality Index questionnaire. They were put to nap for 5 min on three days during the first week, then for 10, 20, and 30 min in the same protocol during the consecutive weeks. After a 1-h class, both the students themselves and their corresponding teachers evaluated the participation level of the participants. They were then divided into two groups, and were instructed to play iPad game ‘Free Flow’. One group took a nap while the other group was prohibited from taking a nap. Both groups were instructed to play the game again. This was repeated once every afternoon for three days. Results: The experiment showed that 20-min nap was superior in subjective evaluations to the other nap duration, and the mean game score differences before and after were significantly higher in the nap taking group after the 20-min nap when analyzed using non-parametric statistical method (p-value 0.04). Conclusions: Therefore, 20-min nap is likely to boost planning domain of executive function on sleep deprived late adolescents. KCI Citation Count: 0